Malay bureaucracy in Japanese administration: Japanese expectations, Malay dilemmas and problems - Fathil, Fauziah (2013)
Following the Japanese occupation of Malaya, a military administration was established. Led by Japanese military officers, the new administration was assisted by the existing local bureaucracy or administrative machinery of which the Malays were the majority. The expectations of the Japanese authority i.e. to obtain cooperation and loyalty from the locals placed the Malay bureaucrats in a tight position. Having to serve the Japanese masters put the Malay civil officers in a dilemma and caused them to endure some problems. Their reluctance to render cooperation would be seen as unfaithful act and thus, liable to be punished or, worse still, given the multi-racial composition of the Malayan society, might result in the Malays as a group losing their special rights or positions to non-Malays. Yet, to work for the Japanese entailed unwanted perceptions or reactions from among their fellow countrymen that they were seen as collaborators of the Japanese or traitors of their own country. Based primarily on library research this paper aims to analyze the difficult position which the Malays bureaucrats or civil servants during the war years were in and the kind of problems and troubles that they were facing from the Japanese and their fellow countrymen alike, particularly the anti-Japanese Malayan Chinese. Japanese expectations and reasons for their recruitment of Malays as administrators in the first place will also be examined. Finally, the findings will highlight that whatever experienced by the Malay bureaucrats during these years partly contributed to the rise of Malay nationalism in the years that followed the end of Japanese occupation in 1945.